Financial Inclusion and Employment in Africa’s Informal Small and Medium Enterprises: The Moderating Role of Mobile Money - Ackom, Enoch Kojo; Ocansey, Evans O. N. D. (European Scientific Journal, ESJ, 2025)
Small and medium-sized enterprises (SMEs) in Sub-Saharan Africa (SSA), particularly those operating within the informal sector, play a crucial role in employment generation. Yet, access to finance remains a critical barrier to their growth. This study investigates the influence of financial inclusion on employment within the informal SME sector, with a particular focus on the moderating role of mobile money services. The study uses a balanced panel dataset covering 38 SSA countries from 2000 to 2023. Financial inclusion is measured through formal account ownership, mobile money usage, and formal savings, while mobile money is captured via a composite index reflecting access, usage frequency, and savings behavior. Employment ratio serves as a proxy for SME employment due to data limitations. Using the two-step System Generalized Method of Moments (GMM), the analysis addresses endogeneity and dynamic effects in panel estimation. Findings show that financial inclusion has a positive but weak impact on employment, while mobile money alone contributes modestly. However, the interaction between mobile money and financial inclusion shows a significant negative effect, suggesting that mobile services may reduce the employment-enhancing effects of traditional financial inclusion if not well-integrated. These findings have important implications for financial policy, SME development, and digital finance regulation in SSA. This study contributes to the growing literature on digital financial inclusion by offering cross-country empirical evidence using dynamic panel estimation. It calls for a more nuanced integration of digital and formal finance tools to optimize employment outcomes in the informal economy.